Development of 4to24, a Transition Application for Parents of Students With Visual Impairments. (November 2021) - Antonelli, Karla; Cmar, Jennifer L.; Steverson, Anne
Introduction: This article focuses on the development of 4to24, an informational app for parents of students with visual impairments, with emphasis on obtaining stakeholder input, developing content, and establishing content validity. The app provides information, resources, and activities to help students, ages 4–24 years, prepare for independence and employment as an adult. Method: App design and content development involved multiple phases of iterative design and writing. Stakeholder input was obtained via an advisory board and user focus groups with parents and students. Experts reviewed and validated content with ratings and recommendations on accuracy, age-appropriateness, and relevance. Results: Advisory board members identified important domains to address in 4to24 including social skills, technology, travel skills, health and fitness, independent living, career education, and self-determination. They recommended focusing on elevating parents' expectations and confidence in supporting and teaching their children. Focus group participants recommended accessibility, ease of use, and relevant information to make the app appealing to users. The content validation process supported the content's relevance, accuracy, and age-appropriateness and resulted in a final count of 410 informational modules. Discussion: Parent involvement and expectations are critical to students' preparation for future employment. 4to24 provides support for parents to collaborate with service providers and reinforce concepts and skills outside of school. Development of the app technology and its large volume of content required a full 5-year process. Implications for practitioners: Lessons learned from this project can inform future resource development projects, including recommendations to start small and define goals early in the process. The 4to24 app is a new resource for parents of students with visual impairments that can supplement services provided by professionals.